The Impact of Online Reviews and Ratings toward Shopee’s Customer Purchase Intention in Gianyar Regency - Tjokorda Gde Agung Wijaya Kesuma Suryawan; I Komang Sumerta; I Gede Alan Vatara; Sharmini Abdullah (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
Purchase intention is one of the aspects that ensures the success of the company's revenue goals. Customers' online purchase intention is confirmed by various aspects, including online customer reviews and online customer ratings. Likewise, for Shopee customers in Gianyar Regency, online customer reviews and online customer ratings are two variables that can influence purchase intention. This study also aims to identify the positive and significant influence between online customer reviews and online customer ratings simultaneously and partially on the purchase intention of Shopee customers in Gianyar Regency. Information collection methods used in this study were observation, interviews and questionnaires. The number of respondents used in this study are 96 people with the method of determining the sample using purposive random sampling. Furthermore, the information was analyzed using quantitative analysis consisting of Research Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Analysis, F-Test and t-Test, using the IBM SPSS Statistic 25 software. The results of the analysis prove that there is a positive and significant influence simultaneously and partially between online customer reviews and online customer ratings on Shopee customer purchase intention in Gianyar Regency. The critical review in this paper can contribute to researchers in the field of marketing, making use of online commerce to explore opportunities for future research gaps, explore various other signals that have not been revealed and develop more diverse future studies.